2018
DOI: 10.1016/j.celrep.2018.05.096
|View full text |Cite
|
Sign up to set email alerts
|

NMDA Receptor Autoantibodies in Autoimmune Encephalitis Cause a Subunit-Specific Nanoscale Redistribution of NMDA Receptors

Abstract: SUMMARY Anti-N-methyl-D-aspartate receptor (NMDAR) encephalitis is a severe neuropsychiatric disorder mediated by autoantibodies against the GluN1 subunit of the NMDAR. Patients’ antibodies cause crosslinking and internalization of NMDAR, but the synaptic events leading to depletion of NMDAR are poorly understood. Using super-resolution microscopy, we studied the effects of the autoantibodies on the nanoscale distribution of NMDAR in cultured neurons. Our findings show that, under control conditions, NMDARs fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
53
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(55 citation statements)
references
References 32 publications
2
53
0
Order By: Relevance
“…Antibody-mediated encephalitis disorders also occur with inflammation and seizures, but compared with other diseases and experimental models, they provide a direct mechanism of synaptic dysfunction and hyperexcitability via specific antibody binding to synaptic receptors and proteins (ref. 92 and Figure 2). Although there are no studies available on the above-described…”
Section: Downstream Synaptic Targets Of Epilepsy-related Inflammationmentioning
confidence: 94%
See 1 more Smart Citation
“…Antibody-mediated encephalitis disorders also occur with inflammation and seizures, but compared with other diseases and experimental models, they provide a direct mechanism of synaptic dysfunction and hyperexcitability via specific antibody binding to synaptic receptors and proteins (ref. 92 and Figure 2). Although there are no studies available on the above-described…”
Section: Downstream Synaptic Targets Of Epilepsy-related Inflammationmentioning
confidence: 94%
“…Antigen Antibody pathogenicity Genetic model NMDAR Internalization of NMDAR, disruption of the interaction of NMDAR with EphB2R. Decreased memory and learning, depressive-like behavior; decreased long-term potentiation (LTP); lowered threshold for seizures (92,101,103,105,107).…”
Section: Table 4 Comparison Of the Pathogenic Effects Of Autoantibodmentioning
confidence: 99%
“…Postsynaptic NMDARs turn over much more slowly, on the hour‐to‐day timescale (Lissin et al, ; Tovar & Westbrook, ; Groc et al, ). NMDAR clusters are 100–200 nm in diameter (Chen et al, ; Hanamura et al, ; Ladepeche et al, ).…”
Section: Postsynaptic Distribution Of Ampars and Nmdarsmentioning
confidence: 99%
“…This differential effect can be explained by experimental in vitro and in vivo analysis that relates the presence of autoantibodies (such as anti-NMDA) that affects the NR2A/2B synthesis at the nanoscale level and alter the correct receptor function causing synaptic internalization, modifyng the electrical activity. These changes are associated with memory impairment and including the temporary rearrangement of the NR2A/NR2B subunits[33]. On the other hand in relation to anti-Sm antibodies and neuronal receptors, it has been demonstrated that these autoantibodies can disrupt BBB and have a potential neurotoxic effect that is considered prognostic factor for acute confusional state (ACS) in SLE [19, 20], however, more evidence is needed to determine the presence and molecular effect of anti-Sm antibodies on NR2A/2B subunits receptors in murine lupus cognitive impairment.…”
Section: Discussionmentioning
confidence: 99%